Atelier science-pratiques-politiques sur la problematique alimentation durable du betail au Senegal - Vadez, Vincent; Bossuet, Jerome (CGIAR System Organization, 2024)
Multistakeholder science-policy dialogue on systemic and climate smart innovation to feed sustainably livestock in Senegal. BRIDGE consortium with CERAAS gathered farmer organisations, researchers, value chain and civil society actors, representative of the Ministry of Agriculture and donor agency to exchange evidence and collaboratively brainstorm action research to improve feed security. Innovations discussed included forage development, dual purpose varieties and crop residue transformation.